Analisis Stilistika Pada Puisi “Perempuan Yang Tergusur” Karya W.S Rendra - Siti Nurullika Gustira (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This research aims to determine the use of language styles, describe the diction and message to be conveyed in the poem "Perempuan yang Tergusur" by W.S Rendra. So also the poem " Perempuan yang Tergusur " is a poem with a theme of protest or social criticism. The problem of this research is how the language style in the poem " Perempuan yang Tergusur " is used by Rendra to voice social criticism of the reality that occurred. The method and theoretical basis used in this research is stylistics. Based on the analysis that has been carried out, the results obtained are that Rendra uses several language styles of similes, comparisons and contradictions to describe the problems presented in the poem.